Geography of Carrion's disease - Rebagliati, Raúl (1937)
Looking at the distribution of the wart on the surface of the Earth, a singular fact imposed immediately: wart exists only in Peru. To date, no fideligno grounds to show the existence of this disease outside of Peru owned.